Práticas pedagógicas em ambiente hospitalar: a contação de histórias na perspectiva das crianças de um centro de oncologia - Ribeiro, Osdi Barbosa dos Santos (2018)
The pedagogical practice of storytelling in the hospital environment consists of a possibility to assure to children in oncological treatment experiences related to playfulness and learning through the processes of socialization and the acts of caring and educating.Based on this statement, this research aimed to understand the meanings attributed by the children of the oncology center, to the pedagogical practices in the hospital environment, especially to storytelling. This study is based on a descriptive qualitative approach. As research techniques, data collection, systematic observation, field diary and semi-structured interview were used. The universe of participants involved children from the Child and Adolescent Oncology Center of the HEC, in Feira de Santana, Bahia. At the first moment, an interview was conducted with a pedagogue of the hospital environment and, in parallel with the systematic observation of pedagogical practices, interviews were conducted with eleven children. Based on the information provided by the pedagogue, the participants were chosen, respecting the condition of the hospitalized child. The research had as theoretical contribution as reference authors such as Elizete Matos and Maria Mugiatti, José Carlos Libâneo, Rosângela Wolf, Christiane Verdi, Nelly Coelho among others that helped to investigate the state of knowledge in relation to object of study. The collected data were analyzed based on content analysis. The syntheses of this study indicate that the pedagogical practices in the hospital environment, as well as their intentionalities, can be characterized based on the educational approach under the aspects of schooling and play. Regarding children's understanding of the experiences of cancer diagnosis and pedagogical practices in the context of the toy library, the data show that, although these practices are developed in the hospital environment, they are more related to the sense that the children attribute to the school than to the hospital. It’s in the toy library that children find elements that bring them closer to the school environment, such as the pedagogical practice of storytelling. This practice emerges as a way to take the child from a reality of silence and isolation to enter a world where the dream is possible, in which fantasy plays this role of transposing beyond the limits imposed by the disease. Thus, it was observed that when the child participates in the pedagogical practice of storytelling, the child assumes the condition of an active and participatory subject, with the possibility of reflecting on what is being lived and breaking with the condition of the patient that the situation of illness and hospitalization confere. Based on the meanings attributed by children, this pedagogic practice consists of a relevant methodological resource in the hospital environment, by providing well-being, effectively promoting development, mitigating the effects of treatment and helping the child to deal better with the situation that is living.In summary, the findings of this research indicate pedagogical practice with a frequency that could be amplified in view of the needs felt by the children to participate in this activity throughout the week. The practice developed in the toy library has no obligation to establish a link with the school, since it isn’t a hospital class. To do so, the data show that the opportunity afforded prevents the children's difficulties until they’re able to return to the school in which they’re enrolled. In addition, the findings suggest the possibility of implanting a hospital class for the more punctual care of this demand in the context under study.